CEREBRAL VESSEL REACTIVITY IN PATIENTS WITH ESSENTIAL ARTERIAL HYPERTENSION - N. N. Ilov; R. N. Schwartz; T. N. Panova (Российский кардиологический журнал)
The study was aimed at assessing the reactivity of cerebral vessels in patients with essential arterial hypertension (EAH) and different stages of blood pressure elevation. In 100 EAH patients, aged 30-60 years, cerebral blood flow parameters were assessed by transcranial Doppler ultrasound and capnometry at rest and during ventilation tests. The parameters of cerebral blood flow auto-regulation (CBFA) were calculated. The hemodynamic response to hyper- and hypoventilation was disturbed in 50 EAH patients (48,6%). Reduced blood vessel reactivity and functional CBFA reserve were explained by a decrease in vasodilatation reserve. The severity of CBFA disturbances positively correlated with EAH stage. The authors suggest that EAH stage could be a risk factor in the development of hemodynamic deficiency of cerebral blood flow.